Corrigendum - Sakai T (Dove Medical Press, 2012)
Sakai T, Kohzaki K, Watanabe A, Tsuneoka H, Shimadzu M. Use of DNA microarray analysis in diagnosis of bacterial and fungal endophthalmitis. Clin Ophthalmol. 2012;6:321–326. The following sentence on page 322 was incorrect in the published paper:"This study was performed in accordance with the Helsinki Declaration of 1975 (1983 revision) and the institutional review boards of Jikei University."The correct sentence should read:"This study was performed in accordance with the Helsinki Declaration of 1975 (1983 revision)."Read the original article